2017
DOI: 10.1016/j.foodres.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Natural fortification of trout with dietary macroalgae and selenised-yeast increases the nutritional contribution in iodine and selenium

Abstract: Fish and seafood consumption are increasing worldwide and the contribution of aquaculture products to consumers' diets is significant. External feeding in aquaculture unlocks the possibility of tailoring fish products with health beneficial compounds. A study was undertaken to evaluate the feed fortification with an iodine-rich macroalgae (Laminaria digitata) and selenised yeast, at its maximum permitted levels, on minerals and vitamins content in rainbow trout edible part. Dietary supplementation resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…Likewise, He et al [ 105 ] found that, compared with pigs under a normal diet, those supplemented with Laminaria digitata over three months accumulated 45% more I in muscle tissue and up to 213% in other internal organs. Similar results were further described in an identical study in which pigs fed with A. nodosum contained 2.7 to 6.8 more I in their muscle and internal organs than those fed under a regular diet [ 106 ].…”
Section: Consumption Of Macroalgaesupporting
confidence: 85%
See 1 more Smart Citation
“…Likewise, He et al [ 105 ] found that, compared with pigs under a normal diet, those supplemented with Laminaria digitata over three months accumulated 45% more I in muscle tissue and up to 213% in other internal organs. Similar results were further described in an identical study in which pigs fed with A. nodosum contained 2.7 to 6.8 more I in their muscle and internal organs than those fed under a regular diet [ 106 ].…”
Section: Consumption Of Macroalgaesupporting
confidence: 85%
“…with Laminaria digitata -fortified fish meal (0.8%) during nine months, caused their total iodine content to be approximately four times higher than that of the control group [ 108 ]. Feeding other species, such as gilthead seabream ( Sparus aurata ) and rainbow trout, with L. digitata -supplemented meals was shown to positively contribute to the increase of their fillets’ iodine content as well [ 106 , 109 ]. These results are of particular importance considering that aquaculture is overcoming the capture fishery supplies and the current trend in aquafeeds for replacing marine-derived ingredients (fish meal and fish oil) by vegetable protein and oil sources (much lower in iodine) can significantly interfere with the fish nutritional profile.…”
Section: Consumption Of Macroalgaementioning
confidence: 99%
“…with L. digitata -fortified fish meal (0.8%) over nine months, contributed to an increase of their total iodine content in approximately four times the levels found in the control fishes. Similar observations were described in other species, such as gilthead seabream ( Sparus aurata ) and rainbow trout, which revealed an increased iodine content in their fillets after L. digitata was introduced in their meals as well [114,115]. An identical experiment carried out with pigs also revealed that the supplementation of L. digitata in the animal’s feed over 3 months resulted in an accumulation of 45% more I in muscle tissue and up to 213% in other internal organs compared to the pigs under a normal diet [116].…”
Section: Use Of Brown Macroalgae As Food Ingredientsupporting
confidence: 77%
“…This is in line with Julshamn et al [45], who described lower incorporation of I in muscle than in liver and kidney of Atlantic salmon that had been raised for 150 days in seawater and fed 54 or 86 mg I kg −1 diet. In accordance with the present results, experiments with rainbow trout in freshwater have shown increased I levels in the fish after feeding different seaweeds and that the I concentration in muscle was dependent on the dietary level of I and the length/percent body weight increase obtained [46,47].…”
Section: Discussionsupporting
confidence: 92%